Investigating youth learning and data: Contexts, concepts, and connections. Issue 1 (1st February 2019) - Acker, Amelia; Bilal, Dania; Bowler, Leanne; Garcia, Patricia; Meyers, Eric M.; Zhang, Yan
ABSTRACT: This panel presents research that has explored young people in relation to data traces in digital, networked platforms supported and made accessible through Internet connected devices, applications, and platforms, asking the question: how might we help youth, as data subjects, gain a sophisticated understanding of data, including the processes involved in data creation, collection, curation, and aggregation with networked devices, platforms, and information services? Panelists will convene around the impact of these new technologies in youths' lives by presenting a range of empirical research on search engines, identity‐based gaming, literacy groupware for children, and data literacy programming for youth in public libraries.